The Effectiveness of Learning Tools Using the 5E Learning Cycle Model to Improve Mastery of Concepts and Generic Science Skills - Ihda Shoumi Nurdini; Suyatno Sutoyo; Pirim Setiarso (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the effectiveness of learning devices using the 5E learning cycle model to improve students' mastery of concepts and generic science skills in electrolyte and non-electrolyte solutions. This research is a type of pre-experimental research with one group pretest-posttest design research design. The research subjects were 21 students of class X MIPA-1 MA YKUI Maskumambang, Gresik, East Java. The methods used in data collection include validation and tests. The research data were analyzed descriptively and the n-gain analysis was used to determine the increase in students' mastery of concepts and generic science skills. The results showed: (1) students' mastery of concepts in electrolyte and non-electrolyte solutions was 0.8 with high criteria; (2) The average score of the students' mastery of concepts on electrolyte and non-electrolyte solutions was 89; (3) Increasing students' generic science skills on electrolyte and non-electrolyte solution material by 0.8 with high criteria; and (4) The average value of generic science skills for observation skills is 96 with predicate A. Based on the results of this study, it can be concluded that the learning device using the 5E learning cycle model is effective in improving students' mastery of concepts and skills in electrolyte and non-electrolyte solution material